Resistensi Antibiotik Bakteri Escherichia coli dari Air Sumur di Peternakan Ayam Desa Suranadi, Lombok Barat - Sopiandi Sopiandi; Kholik Kholik; Candra Dwi Atma; Munawer Pradana; Gracia Angelina Hendarti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Antimicrobial Resistance (AMR) has become a global health problem. Escherichia coli bacteria in water can act as a reservoir for the spread of antibiotic resistance. The study aimed to determine the resistance of Escherichia coli isolated from well water in chicken farms to antibiotics. The study design was an observational survey conducted from November to December 2022 at five chicken farms in Suranadi Village, Narmada District, West Lombok Regency. Five well water samples used in the study came from five wells in chicken farms located 10 meters from the chicken coop. 250 ml of well water samples were taken, put into sterile bottles, and then taken to the Health Laboratory Testing and Calibration Center of West Nusa Tenggara Province for isolation of Escherichia coli. Escherichia coli was isolated by planting on Eosin Methylene Blue Agar (EMBA) and identified using gram staining and biochemical tests. Antibiotic susceptibility testing of Escherichia coli was conducted using the disc diffusion method using five antibiotics: Gentamicin, Tetracycline, Amoxycillin, Chloramphenicol, and Ciprofloxacin. This study successfully isolated four Escherichia coli from five well water samples. The susceptibility test results showed that 75% of the Escherichia coli isolates were resistant to Amoxycillin, 50% to Ciprofloxacin, and 25% to Chloramphenicol. The Escherichia coli isolates were still sensitive to Gentamicin and Tetracycline.